Indication of feeding ground inside the Manta Ray's cleaning station by investigation of the zooplankton community composition in Raja Ampat Islands, Indonesia - WIDIASTUTI WIDIASTUTI; DEBBY BORUMEI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Widiastuti, Borumei D. 2024. Indication of feeding ground inside the Manta Ray's cleaning station by investigation of the zooplankton community composition in Raja Ampat Islands, Indonesia. Biodiversitas 25: 1239-1245. Raja Ampat Islands, Indonesia, hosts reef manta ray (Mobula alfredi) and oceanic manta ray (Mobula birostris). Studies reported that these areas have functioned as manta ray cleaning and nursery sites. However, food availability is also the main attraction for manta ray aggregation. Thus, this study investigated the zooplankton community composition and abundance in the Manta Sandy Spot, a manta's cleaning station, to indicate its other role as the manta ray's feeding ground. Three sampling sites were located around the cleaning station bordered by mooring. A plankton net collected samples with a 100 µm mesh size, a mouth diameter of 30 cm, and a 1 m length horizontally towed from a boat for 5-10 min at a speed of ~2 knots. Manta ray's behavior was observed by snorkeling in the surface waters. Results demonstrated that the zooplankton was only composed of Copepod, consisting of three orders: Calanoida, Cyclopoida, and Harpacticoida. Among these orders, Calanoids dominated the zooplankton composition (93%). These genera were further grouped according to their body sizes, whereas three genera in Calanoids (Eucalanus, Calanus, and Undinula) were categorized as large-bodied zooplankton. The presence of the large-bodied zooplankton in the water samples, Calanoids, and Cyclopoids, which have been reported as the manta rays' preferred prey, indicates the area's role as the manta ray's feeding ground. This finding is supported by studies that found these zooplankton in the water where manta rays' feeding activity occurred and were absent in areas with no feeding activity. More indications were demonstrated by the manta ray's behavior, which followed the feeding activity criteria.